Influence of COVID-19 pandemic on the psychological status of infertile couples. (October 2020) - Esposito, Veronica; Rania, Erika; Lico, Daniela; Pedri, Sara; Fiorenza, Alessia; Strati, Marina Francesca; Conforti, Alessandro; Marrone, Vinenzo; Carosso, Andrea; Revelli, Alberto; Zullo, Fulvio; Di Carlo, Costantino; et al.
Highlights: No data are available to the distress of infertile couples during COVID-19. Stop performing ART treatments during COVID-19 contributed to increase anxiety. The psychological impact was more severe for women than for men. Psychological impact of COVID-19 in infertility couple should not be underestimated. Abstract: Objective(s): to evaluate the impact of the COVID-19 pandemic on infertile couples' emotions, anxiety and future plans. Study design: An observational study was perfomed by Italian ART centers and online forums. In this study, infertile couples candidate to ART and whose treatment was blocked due to the COVID-19 lockdown were enrolled through an online survey. The psychological impact of COVID-19 was measured by Impact of Event Scale-Revised (IES-R) and by a short form of the Spielberger State-Trait Anxiety Inventory (STAI); Self-perceived anxiety related either to pregnancy safety and to economic crisis measured by VAS scale. Results: 627 patients completed the survey. The COVID-19 lock-down had a moderate/severe psychological impact on infertile patients (mean IES-R score 36.4 ± 16.6). The mean STAI score was 49.8 ± 15.3, with an overall incidence of STAI > 36 of 71 %. The mean VAS scale for anxiety perception was 45.3 ± 15.3. Women were more emotionally distressed, anxious and depressed than men (36.8 ± 16.4 vs 31.0 ± 18.4 for IES-R, respectively; p = 0.03). Notwithstanding the uncertainty about pregnancy safety, 64.6 % of respondents chose to maintain their reproductive programme. Economic crisis induced 11.5 % of the surveyed patients to give up their ART program. Respondents who had at least one relative affected by COVID-19 had a significantly higher IES-R score and anxiety VAS, but not higher STAI scores, than patients belonging to unaffected families. Conclusion(s): COVID-19 pandemic itself and the recommendation to stop ART program generated higher distress levels in infertile couples. The psychological impact of COVID-19 pandemic in infertility patients should not be underestimated, and a specific psychological support should be planned.